Community Empowerment Through Tourism Awareness Group (POKDARWIS): Study On The Development Of Pasir Putih Tourism Village (WPP) In Dalegan Village, Panceng Sub-District, Gresik Regency - Islamiyah, Mufidatul; Ariefianto, Lutfi; Fajarwati, Linda (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
This study aims to identify and describe community empowerment efforts through tourism awareness groups (POKDARWIS) in the development of Pasir Putih Tourism villages (WPP) in Dalegan Village, Panceng Sub-District, Gresik Regency. This study uses a descriptive type of research with a qualitative approach. Determination of the location using a purposive area, located in the Pasir Putih Tourism Village, Dalegan Gresik. The technique of determining the informants is purposive sampling, for data collection using interview, observation and documentation techniques. Checking the validity of the data using the observation extension technique, increasing persistence, triangulation data source and triangulation technique. Data analysis uses the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that community empowerment efforts have been carried out quite well through three stages, called enabling, empowering, and protecting. The development of this tourist village is driven by the natural and cultural potential, the physical environment, and the economic potential which have been utilized quite well through the actions taken by Pokdarwis so as to be able to develop potential in the community.